(untitled) (International Seven Journal of Multidisciplinary, 2024)
The digital transformation of Brazilian SMEs is essential to maintain competitiveness in the current market, especially after the challenges imposed by the COVID-19 pandemic. Adopting digital technologies enables these businesses to better connect with customers, increase operational efficiency, and innovate quickly. However, the transition faces significant obstacles, such as a lack of skills and resistance to change. With well-planned strategies, digitalization can bring great economic benefits and sustainable growth in the future.